TURTLE CONSERVATION CAMPAIGN AS A TOURIST ATTRACTION FOR BALI - Lisa Harry Sulistiyowati; Siska Ernawati Fatimah; Acep Komara; M. Yudi Mahadianto; Sanchita Saha; Dien Noviany Rahmatika (Transpublika Publisher, 2024)
Most sea turtle species around the world are threatened with extinction. The threat of sea turtle extinction is largely caused by humans for consumption, souvenirs, trade, medicine and religious activities as well as for commercial purposes such as the sale of eggs, meat and shells. This human behavior is threatening sea turtle populations. Preventing the decline of these threatened sea turtle populations requires changes in human behavior that are educated through conservation campaigns. This international service was carried out with the aim of recognizing local culture and local wisdom products and participating in painting traditional Thai pottery. This activity is a community service activity that collaborates between the Faculty of Economics and Business of Swadaya Gunung Jati University Indonesia, Panca Sakti Tegal University Indonesia, Suan Dusit University and Eastern Instutite for Integrated Learning in Management University India. Community service activities were carried out in Nong Nooch Thailand, with a total of 25 participants consisting of 10 students and 15 lecturers. Sea turtle conservation is one of the community's efforts to preserve the environment and sea turtle habitat for the survival of sea turtles